Small ruminants network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A network for research on small ruminants, to cover the whole of the African continent, has been set up as the result of a meeting in Bamenda, Cameroon, in January 1989. Sponsored by ILCA and funded by GTZ, the International Foundation for Science...